2013
DOI: 10.7727/wimj.2012.105
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia Gravis in South Trinidad

Abstract: While many features of MG in South Trinidad were similar to international data, the unique, statistically significant higher prevalence in Africans than East Indians warrants further research, given the paucity of reports from Africa and India. Patients with MG suffered a diminished quality of life, necessitating improved health planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
1
5
0
3
Order By: Relevance
“…In our study, we identified 14 cases in 4 years and 10 months between March 2012 and January 2017. We found a female predominance with a ratio F/M 1.3, a predominance in young adults (<50 years), and only two cases each of late MG and juvenile MG (<15 years) were recorded, which is in line with data from the literature [12][13][14][15][16][17][18][19][20]. Sex hormones appear to play a central role and some studies involve estrogens as the main mediator of the disease [21,22].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In our study, we identified 14 cases in 4 years and 10 months between March 2012 and January 2017. We found a female predominance with a ratio F/M 1.3, a predominance in young adults (<50 years), and only two cases each of late MG and juvenile MG (<15 years) were recorded, which is in line with data from the literature [12][13][14][15][16][17][18][19][20]. Sex hormones appear to play a central role and some studies involve estrogens as the main mediator of the disease [21,22].…”
Section: Discussionsupporting
confidence: 86%
“…Sex hormones appear to play a central role and some studies involve estrogens as the main mediator of the disease [21,22]. At the beginning, MG is influenced by sex and age in a bimodal way: in women under 40, women predominate, but in the fifth decade cases are equally divided between men and women, and after 50 years, new cases are slightly more frequent in men [7,[16][17][18]22,23]. This characteristic has also been observed in our patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Les séries d'ASS, comme la nôtre, avec une moyenne d’âge de début de la maladie entre 25 ans et 32 ans [ 29 , 30 , 34 ], confirment cette tendance à un début plus précoce de la MAI dans les populations noires. La même tendance est observée en Chine [ 35 ], Singapour [ 2 ], Trinidad et Tobago [ 23 ]. Par contre en Iran [ 32 ] et aux Pays-Bas [ 6 ], une moyenne d’âge de début après 40 ans est notée.…”
Section: Discussionunclassified
“…La symptomatologie clinique initiale de la MAI, tous âges confondus, débute habituellement dans 60 à 85% des cas par une atteinte oculaire, dans 15 à 17% des cas par une atteinte de la musculature d'innervation bulbaire ou faciale et dans 10% des cas par un déficit de la musculature axiale ou périphérique [ 8 , 15 , 23 ]. Dans notre série, le même profil clinique révélateur a été observé, cependant à des fréquences plus élevées pour les atteintes bulbaires et des membres, liées à des biais d'imprécisions dans la chronologie de l'histoire de la maladie favorisés par les longs délais diagnostiques dans notre contexte.…”
Section: Discussionunclassified